Pengaruh Gaji Dan Insentif Terhadap Kinerja Karyawan Pada PT Muhandas Permata Sarana Cilandak Jakarta Selatan - Dicky Hadi Pratama; Kamsidik Kamsidik (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the effect of salary and incentives on employee performance at PT Muhandas Permata Sarana, both partially and simultaneously. The research was conducted using a quantitative research method involving employees as the sample. The sample used was a saturated sample, with a total of 62 respondents. This study employed several statistical tests, including validity test, reliability test, classical assumption test, correlation coefficient test, regression coefficient test, coefficient of determination test, and hypothesis testing. The results of the study produced a multiple linear regression equation: Y = 15.599 + 0.298X₁ + 0.459X₂ + e. The regression coefficient value of the performance variable (Y) is 15.599, which implies that if Salary (X₁) and Incentives (X₂) remain unchanged, the consistent value of employee performance will be 15.599. Based on the t-test results, the effect of Salary on Performance shows a t-value of 3.086 > 2.001 with a significance level of 0.003 < 0.05. Therefore, H₀ is rejected and Hₐ is accepted, indicating that salary has a positive and significant partial effect on employee performance. Similarly, the effect of Incentives on Performance shows a t-value of 5.027 > 2.001 with a significance level of 0.000 < 0.05. Thus, Hₐ is accepted and H₀ is rejected, indicating that incentives also have a positive and significant partial effect on employee performance. The F-test results for the combined effect of Salary and Incentives on Performance show an F-value of 17.928 > 3.150 with a significance level of 0.000 < 0.05. This indicates that the hypothesis stating that salary and incentives simultaneously influence employee performance is accepted